Cultural Codes of Marriage Rituals in Anatolia: From Ritual to Word in the Context of Oral Culture - Atila Kartal (Religions)
Marriage is a social contract that carries a number of qualities recognized as having fundamental values. These qualities include a spiritual bond between spouses, mutual love, affection, and responsibility, the continuation of the generation, and the existence of social order. The social definition of marriage implies that it is a phenomenon that occurs not only between two individuals in the context of cultural continuity but also in other social structures. It evolves into a structure that encompasses not only the initial two families but also the broader societal context. In Islamic marriage, a contract is formalized between a man and a woman who meet the religious requirements for marriage. The contract is executed with their consent and in the presence of witnesses. However, from a cultural perspective, marriage embodies a multifaceted structure, influenced by religion, ritual practices, symbols, and traditions. In this study, topics such as oral culture, wedding traditions, and rituals are discussed, and cultural practices are interpreted. This study sheds light on the manner in which marriage rites influence the discourse and actions within the social structure. Such studies are of paramount importance in demonstrating the continuity and vitality of culture, as well as the transformative nature of ritual meanings over time. They underscore the notion that culture is an ever-evolving process of interpretation, a characteristic that is intrinsic to its very essence. These actions, inextricably linked to societal structures, have the potential to give rise to novel symbolic meanings and values at any given juncture. However, it is imperative to recognize that the mere analysis of texts representing oral culture products is insufficient for comprehending their ritual functions, social messages, and emotional dimensions. Consequently, an interdisciplinary approach that incorporates the study of transitional rituals and oral culture is necessary to achieve a more comprehensive understanding. By examining cultural elements from diverse perspectives, we can develop a more comprehensive and nuanced understanding of cultural diversity in Anatolia.